An Unsymmetrical Squaraine‐Based Activatable Probe for Imaging Lymphatic Metastasis by Responding to Tumor Hypoxia with MSOT and Aggregation‐Enhanced Fluorescent Imaging. Issue 72 (5th December 2019) - Lin, Yi; Sun, Lihe; Zeng, Fang; Wu, Shuizhu
Abstract: Optoacoustic imaging has great potential for preclinical research and clinical practice, and designing robust activatable optoacoustic probes for specific diseases is beneficial for its further development. Herein, an activatable probe has been developed for tumor hypoxia imaging. For this probe, indole and quinoline were linked on each side of an oxocyclobutenolate core to form an unsymmetrical squaraine. A triarylamine group was incorporated to endow the molecule with the aggregation enhanced emission (AEE) properties. In aqueous media, the squaraine chromophore aggregates into the nanoprobe, which specifically responds to nitroreductase and produces strong optoacoustic signals due to its high extinction coefficient, as well as prominent fluorescence emission as a result of its AEE feature. The nanoprobe was used to image tumor metastasis via the lymphatic system both optoacoustically and fluorescently. Moreover, both the fluorescence signals and three‐dimensional multispectral optoacoustic tomography signals from the activated nanoprobe allow us to locate the tumor site and to map the metastatic route. Abstract : Sound and vision : An activatable nanoprobe based on unsymmetrical‐squaraine has been developed for tumor hypoxia imaging, which specifically responds to nitroreductase and produces strong optoacoustic signals due to high extinction coefficient and prominent fluorescence emission arising from the AEE feature. 3D multispectral optoacoustic tomography signals could be obtained for locating the tumor site and mapping metastatic route.